Manfaat dan Mafsadat Teknologi Modern Persfektif Maslahah - Zainuddin; Gassing, Qadir; Kurniati (UNES Law Review, 2023)
This article discusses the benefits and benefits of modern technology from a maslahah perspective which aims to provide an explanation regarding the benefits of modern technology on the development of Islamic law, and how it has a negative influence on the development of Islamic law. This article is a literature review sourced from several relevant references to the topic discussed. Data collection techniques come from researching relevant reference sources in the form of journals, articles, websites, books and other scientific works. Islam has full care and attention for its ummah so that it continues the process of exploring the potential of nature and the environment to become the center of a glorious civilization. In this context, there is no conflict between science and Islam, where both work in balance and harmony to create scientific treasure and human civilization that is better than before. Current technological advances cannot be separated from people's lives. We can now know various information that occurs in various parts of the world directly thanks to technological advances (globalization). Previously, we knew the saying "the world is not as wide as a moringa leaf", now that saying should be changed to today's world as wide as a moringa leaf, because the rapid access to information in various parts of the world makes this world seem narrower because we can see what is happening in America for example, even though we are in Indonesia.